2015
DOI: 10.1371/journal.pone.0123479
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Rational Management of Diarrhea in an Endemic Setting: Observation from India

Abstract: BackgroundDecades after the establishment of clear guidelines for management, mostly due to irrational approach, diarrhea is still a major concern in the developing world, including India. The scenario is even worse in urban slums owing to poor health-seeking and socio-environmental vulnerability. Determining the distribution of rational diarrhea management by practitioners and identification of its important predictors seemed urgent to minimize the potential for antibiotic resistance, diarrhea-related mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…As seen in Table 4, the likelihood that mothers/caregivers will engage in selfmedication behaviour due to their knowledge of the medical condition was 10% (1-0.9x100) lower than that of going. Despite this being the case, the results of the FGD and findings from other researchers revealed that previous knowledge of the diarrhoea condition which was obtained from the health facility, pharmacist and from family and friends had a greater influence on the ability of the mothers/caregivers to administer drugs on their own (Masangwi et al, 2016;Mahapatra et al, 2015).…”
Section: Determinants Of Antimicrobial Use In Diarrhoea Managementmentioning
confidence: 91%
See 1 more Smart Citation
“…As seen in Table 4, the likelihood that mothers/caregivers will engage in selfmedication behaviour due to their knowledge of the medical condition was 10% (1-0.9x100) lower than that of going. Despite this being the case, the results of the FGD and findings from other researchers revealed that previous knowledge of the diarrhoea condition which was obtained from the health facility, pharmacist and from family and friends had a greater influence on the ability of the mothers/caregivers to administer drugs on their own (Masangwi et al, 2016;Mahapatra et al, 2015).…”
Section: Determinants Of Antimicrobial Use In Diarrhoea Managementmentioning
confidence: 91%
“…Diarrhoeal disease can be prevented by simple measures like personal hygiene and environmental sanitation; nonetheless, antibiotic therapy remains one of the common measures used to curb the disease despite the presence of less invasive solutions such as the Oral Rehydration Salts which are key remedies in treating childhood diarrhoea (Padhy et al, 2017;Mahapatra et al, 2015;Gwimile et al, 2012). This key role of antibiotics has contributed to high usage of antibiotics in management of diarrhoea which is contributing to increased cases of antimicrobial resistance (Padhy et al, 2017;Alghadeer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of national policies and strategies related to antibiotic use is associated with increased antibiotic use in acute diarrhea [13]. Factors that in uence appropriateness of antibiotics use in acute acute diarrhea include diagnostic uncertainty, giving something more than just ORS to satisfy the patient, insu cient number of quali ed and competent staff, caregiver preference, source of updating knowledge, experience of the prescriber, age of the child, lack of speci c medicines' information (e.g., clinical guidelines and drug bulletins),lack of continuing medical education and supervision, peer pressure (where senior staff may set inappropriate prescribing practices that are followed by junior staff), lack of diagnostic support services (e.g., laboratory services), poor infrastructure [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Once health care is accessed, affordable and effective interventions exist in the form of oral rehydration therapy (ORT) combined with oral zinc supplements. When these treatments are given in a timely manner they represent the optimal approach for curtailing mortality [14,15,16]. A critical factor in the survival of these cases is therefore the level of maternal understanding of the effective options for home-based management and the symptoms that signal the need to access health-care [13][14][15][16][17]18,19].…”
Section: Introductionmentioning
confidence: 99%
“…When these treatments are given in a timely manner they represent the optimal approach for curtailing mortality [14,15,16]. A critical factor in the survival of these cases is therefore the level of maternal understanding of the effective options for home-based management and the symptoms that signal the need to access health-care [13][14][15][16][17]18,19]. Practices that conflict with the World Health Organization (WHO) treatment guidelines for the management of childhood diarrhoea [20] are sometimes relied upon in the home and include restriction of fluids, breast milk and/or food intake during diarrhoea episodes, and incorrect use of medicines [21,22].…”
Section: Introductionmentioning
confidence: 99%